Control of π–π stacking in carbazole-benzimidazo〈1, 2-f〉phenanthridines: the design of electron-transporting bipolar hosts for phosphorescent organic light-emitting diodes. Issue 10 (12th February 2020) - Chen, Yu-Hsin; Chen, Chia-Hsun; Chang, Chun-Ming; Fan, Bo-An; Chen, Deng-Gao; Lee, Jiun-Haw; Chiu, Tien-Lung; Chou, Pi-Tai; Leung, Man-kit
Abstract : The planar benzimidazo〈1, 2- f 〉phenanthridine moieties form effective electron transport channels through pi-stacking. Abstract : Two bipolar hosts, 8-cbzBIFP and 10-cbzBIFP, both with basic skeletons of orthogonally-connected carbazole and benzimidazo〈1, 2- f 〉phenanthridine (BIFP ) have been prepared. The planar structure of the BIFP moiety governs the molecular stacking in the crystal lattice. Electron transport properties, in comparison to the benzimidazole derivatives, are facilitated. Both hosts display fabulous performances in phosphorescent organic light-emitting diodes with bis(2-phenylpyridine)(acetylacetonate)iridium(iii ) as an emitter. The optimized green PhOLED of 10-cbzBIFP achieves the maximum brightness ( L max ) of 58 810 cd m −2, the maximum current efficiency ( η c ) of 87.0 cd A −1 and external quantum efficiency (EQE) of 21.1%. Likewise, 8-cbzBIFP shows an L max of 58 870 cd m −2, η c of 77.3 cd A −1 and EQE of 19.1%.